Small business management : an applied approach - Mazzarol, Tim , 1957-; Reboud, Sophie (Tilde University Press, 2011)
The aim of this text is to familiarise students with the theory and practice of small business management and challenge assumptions that may be held about the way small business management can or should adopt the management practices of larger firms